Effects of graduated compression socks on ankle inversion proprioception of half-marathon runners at different running distances. Issue 6 (June 2022) - Chang, Lin; Fu, Silin; Wu, Sam; Witchalls, Jeremy; Adams, Roger; Waddington, Gordon; Han, Jia
Abstract: Objectives: To determine the effect of graduated compression socks on ankle proprioception and the relationship between fatigue and ankle proprioception measures in half-marathon runners at successive 7 km intervals during a 21-km run. Design: Repeated measures study. Methods: Twenty well-trained half-marathon runners (mean ± SD: age 38.6 ± 11.3 y, weekly volume 42.3 ± 21.1 km, training experience 4.7 ± 3.5 y) performed two 21 km running trials on a treadmill wearing either graduated compression socks or looser, standard non-compression running socks. Each running trial was divided into three self-paced 7 km blocks, repeated at the same pace for each trial, heart rate was not controlled, but after each block, heart rate, blood lactate, rating of perceived exertion, and ankle inversion proprioception were measured, the latter by using the active movement extent discrimination apparatus. Results: There was no differences between the graduated compression sock and non-compression running sock conditions in rating of perceived exertion scores (F = 0.524, p  = 0.478), heart rate (F = 0.001, p  = 0.975) and blood lactate (F = 0.004, p  = 0.951). Overall, wearing graduated compression socks was associated with significantly better ankle proprioception after 21 km of running ( p  = 0.024, 95% CI = −0.066, −0.005). Heart rate, rating of perceived exertion and blood lactate were not correlated with ankle proprioception sensitivity in the graduated compression sock and non-compression running sock conditions at any point during the run (all p  > 0.05). Conclusions: Wearing graduated compression socks provides a positive effect on proprioceptive control of the ankle joint only after 21 km and may therefore reduce the possibility of injury associated with proprioceptive ability diminishing over time during exercise.